A sustentabilidade no agronegócio a partir de uma análise jurídica - Paulo, Thalita Brunelli de (2021)
This study deals with the global need for the implementation of sustainability by the public and private sectors, aiming to develop a fairer society and an ecologically balanced environment. In this sense, it demonstrates the importance of agribusiness in this implementation, in view of its relevance in the world, as well as the impacts it produces in the social, economic and environmental spheres. Thus, the individual concept of sustainability and agribusiness is outlined, tracing a brief historical evolution, concepts and objectives down to the roots of the new sustainable agribusiness. It is understood how this business model is designed, mainly addressing its contradictions and challenges. It understands its legislative offensive in favor of agribusiness, as well as how the law, in its legislative and economic aspect, has been treated by agribusiness and its interests. Based on these considerations, we sought to verify the direct action of the principle of sustainable development, for the benefit of agribusiness, but that violates socio-environmental rights. It is concluded that the sector needs specific legal support, capable of analyzing and executing sustainable development, combined with a multidisciplinary study. The present work was constituted as a qualitative research and was studied using two methods, namely, dialectical and analytical.